2018
DOI: 10.1590/0037-8682-0506-2017
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in patients with multidrug-resistant Pseudomonas aeruginosa infections: a meta-analysis

Abstract: Pseudomonas aeruginosa is the leading cause of nosocomial infections with high mortality rates owing to the limited therapeutic options for multidrug-resistant Pseudomonas aeruginosa (MDRPA) and metallo-beta-lactamase (MBL)-producing strains. Herein, we present a meta-analysis exploring the association between MDRPA and São Paulo MBL-1 (SPM-1)-producing strains vs. mortality. Online databases were screened to identify studies published between 2006 and 2016. A total of 15 studies, comprising 3,201 cases of P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 27 publications
5
32
1
1
Order By: Relevance
“…Our data demonstrate the predomination and wide spread of SPM-1 MDR/XDR strains in Brazilian hospitals and with the increasing transmission trend of ESBLs CTX-M and OXA variants genes worldwide, as previously reported [20,23,45,76,81,82]. Finally, our results highlight the impact of horizontally acquired resistance mechanisms, mainly ESBLs and class B MBL, in the increasing resistance rates and its commonly association to MDR/XDR P. aeruginosa strains [18,21,23,79].…”
Section: Plos Onesupporting
confidence: 85%
See 2 more Smart Citations
“…Our data demonstrate the predomination and wide spread of SPM-1 MDR/XDR strains in Brazilian hospitals and with the increasing transmission trend of ESBLs CTX-M and OXA variants genes worldwide, as previously reported [20,23,45,76,81,82]. Finally, our results highlight the impact of horizontally acquired resistance mechanisms, mainly ESBLs and class B MBL, in the increasing resistance rates and its commonly association to MDR/XDR P. aeruginosa strains [18,21,23,79].…”
Section: Plos Onesupporting
confidence: 85%
“…These findings emphasize the growing global trend on antibiotic resistance been reported by several studies and rises concern, especially in Latin America countries, where carbapenems still remains as the main choice for the treatment of infections by MDR P . aeruginosa [ 21 , 22 , 23 , 79 , 80 ]. A reduced number of transmissible resistance markers were detected among tested isolates, with bla CTX-M1 (20.4%– 11/54) as the most frequent, followed by bla SPM-1 (5/54–9.2%), bla OXA-2 (3/54–5.5%) and bla OXA-10 (3/54–5.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the mortality of C. auris was also compared with other drug-resistant organisms, which spread in similar ways in healthcare centers. A meta-analysis showed that the mortality of patients infected with multidrug-resistant Pseudomonas aeruginosa was 44.6% [ 76 ]. Besides, the overall mortality of BSIs of vancomycin resistant Staphylococcus aureus and carbapenem-resistant Klebsiella pneumoniae were 26.8 and 54.3% respectively [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa account for 13–19% of hospital acquired infections (HAIs) each year in the US. Mortality rates between 2007 and 2009 was estimated 46.1%) [ 12 , 13 ]. MDR— P. aeruginosa isolates in South America and Malaysia were estimated as 8.2% and 6.9%, as well [ 4 ].…”
Section: Introductionmentioning
confidence: 99%